IMPLEMENTASI METODE OUTDOOR LEARNING DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Nasution, Zulfan Kamal; Julia; Nurdinah Hanifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Student motivation in social studies on local environmental topics remains low due to teacher-centered learning and limited contextual experiences. This study examines the implementation of outdoor learning to enhance motivation and student responses in fourth-grade students at SDN Gudang Kopi I, while describing the planning and execution of the learning process. The study employs a qualitative case study approach, focusing on a single context in depth. Data were collected through semi-structured interviews, direct observation of outdoor activities, field notes, and supporting documentation, then analyzed descriptively. Findings indicate that outdoor learning was structured with teaching modules, task division, and the use of the surrounding environment as a learning resource. Implementation increased student motivation, reflected in active participation, focus, curiosity, willingness to ask questions, and engagement. Students also showed positive responses to this learning experience. The study concludes that outdoor learning effectively transforms abstract content into concrete experiences, strengthening motivation, engagement, and positive student responses. Implications highlight the importance of systematic teacher planning, guidance during field activities, and the use of the environment as a contextual learning laboratory in social studies instruction.